Supply chains and responsibility for OHS management in the Western Australian resources sector - Bahn, S.; Rainnie, Alistair (Emerald Group Publishing Limited, 2013)
Purpose - The purpose of this paper is to analyse human resource supply chains and the responsibility of occupational health and safety (OHS) management using Australian evidence from two unrelated research studies in the resources sector. Design/methodology/approach - The analysis is based on additional findings from the research projects using qualitative case study methodologies. The paper draws on interviews with the underground mining manager in study 1 and the OHS manager in study 2, together with current literature on supply chains and OHS responsibility in Australia. Findings - The paper uses examples drawn from two research studies conducted in the resources sector in 2011 to present the notion that there has been a shift in responsibility and management of OHS from the top of the supply chain to the bottom. Research limitations/implications - The paper draws on two unrelated studies that investigated different issues in OHS management. There is a need to undertake specific research to confirm the argument that suggests that the OHS management systems are improving for the bottom of the human resources supply chain in the resources sector. Practical implications - Findings suggest that in the middle tier resources sector the bottom of the human resources supply chains have robust OHS management systems and induction training, contrary to the weakening of OHS management in typical supply chains in other sectors. Originality/value - Unlike manufacturing, healthcare, the public sector and transport, there is little research conducted in the resources sector researching supply chains and OHS management. This paper provides limited evidence of a differing picture in the resources sector than other industries; however, it argues that further studies should be conducted.